PENDAMPINGAN PENGUATAN PROFIL USAHA UMKM PENGOLAHAN BERBASIS UBI KAYU DI DESA M SITIHARJO KECAMATAN TUGUMULYO KABUPATEN MUSI RAWAS - Febrina Nur Annisa; Ira Primalasari (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
ABSTRACTThe aim of this PKM activity is to make efforts to strengthen cassava-based processing business actors/craftsmen in M. Sitiharjo village, Tugumulyo District, Musi Rawas Regency through outreach, training and mentoring activities in strengthening profiles such as permits, brands and packaging; preparation of bookkeeping; dynamics in KUB; utilization of online marketing channels; and product development/differentiation. The stages carried out in this activity are, the preparation stage, the socialization stage and the evaluation stage. The implementation of community service in the M. Sitiharjo Village/Subdistrict, Tugumulyo District, Musi Rawas Regency, which was carried out by the Lecturer Team of the Agricultural Socioeconomic Study Program, Faculty of Economics and Business, PGRI Silampari University, took place smoothly and in a conducive atmosphere. Next, PIRT licensing and halal certification are arranged by partners so that program sustainability can be implemented and provide benefits for partners such as increasing the quality and selling value of products, increasing consumer confidence and buying interest, expanding distribution areas, increasing product sales, and improving the welfare of the community in village M. Sitiharjo. Apart from that, something that emerged during the PKM implementation was the open, adaptive and enthusiastic attitude of the participants. This attitude caused the approximately 6 hours of PKM activities to pass quickly. This situation, the potential for businesses to develop, the hopes expressed by participants that this PKM activity will continue, as well as the existence of government policies to encourage the downstreaming of various products are the basis for consideration for the team to continue PKM activities in the cassava-based home industry business group. is in the M.Sitiharjo sub-district.Keywords :Profile, MSMEs, Cassava, Halal Certification,BRN